Exposure characteristics of common chemical pollutants and health risk assessment in indoor air of barber shops and beauty salons in Liaocheng City - Yinglin DU; Xiao ZHANG; Rubin ZHOU; Yan WANG; Yuanyuan JIANG; Dejun WANG; Yanxin GAO (环境与职业医学, 2023)
BackgroundThe presence of formaldehyde, ammonia, benzene, toluene, and xylene in indoor air of public places has been confirmed to cause health damage. The employees of barber and beauty shops are exposed to relatively enclosed space for a long time, and could surfer more serious health risks from indoor air chemical pollutants.ObjectiveTo analyze the concentrations of common indoor air chemical pollutants in barber shops and beauty salons in Liaocheng City, and explore potential health risks of the pollutants for employees.MethodsUsing a stratified randomized sampling method, 8 to 10 barber shops and 5 to 10 beauty salons were selected in the main urban area of Liaocheng City to conduct monitoring of the sanitary conditions of public places in winter and summer every year from 2016 to 2021; the indoor air concentrations of formaldehyde, ammonia, benzene, toluene, and xylene in the selected sites were measured, and a questionnaire survey was conducted to collect exposure characteristics of indoor pollutants. The concentration distributions of the five chemical pollutants were obtained from the monitoring data for 6 consecutive years, and the health risk assessment model recommended by the U.S. Environmental Protection Agency was used to perform health risk assessment of inhalation exposure.ResultsIn 2016–2021, the median indoor air concentrations of formaldehyde, ammonia, benzene, toluene, and xylene in the two types of sites were lower than the limits of Hygienic Indicators and Limits for Public Places (GB 37488-2019), but the concentrations of some monitoring sites were higher than the limits. The disqualification rates of the five pollutants in the barber shops were 16.8%, 2.7%, 2.4%, 6.4%, and 12.0%, respectively. The disqualification rate of formaldehyde was the highest in all pollutants (22.0%), while the disqualification rates of ammonia, toluene, and xylene were 1.3%, 2.0%, and 2.0% in beauty salons respectively. Both formaldehyde and benzene were found to have carcinogenic risks (CR) in the two types of public places. Both median values of CR were greater than 1.0×10−6, and both maximum values were greater than 1.0×10−4. Formaldehyde had the highest non-carcinogenic risk in the indoor air of barber shops and beauty salons. The median non-carcinogenic hazard quotients (HQ) of formaldehyde were both greater than 1, and the maximum values were 16.72 and 12.19 times of the standard value; ammonia and toluene had the lowest non-carcinogenic risks, and their maximum values of HQ were less than 1; the median HQs of benzene and xylene were far less than 1, but their maximum risk values of barber shop were greater than 1.ConclusionFor the sake of worker's health, formaldehyde and benzene should be the indoor air pollutant control priority for barber shops and beauty salons in Liaocheng; formaldehyde poses the most serious health hazard to practitioners and should be given high attention and necessary measures to reduce the hazard; benzene poses certain carcinogenic risks, with some of its highest values exceeding 10−4, which is higher than the recommended safety threshold.